2015
DOI: 10.1038/srep15995
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of early loading versus conventional loading of dental implants

Abstract: The aim of this study was to determine the clinical differences between early and conventional loading protocols for dental implants. A comprehensive search of the Medline, Embase, and OVID databases for studies published through January 10, 2015 was conducted. Fourteen studies were included in our analysis. We found that early loading imposed a significantly higher risk of implant failure than did conventional loading (risk ratio = 2.09, 95% confidence interval [CI] [1.18, 3.69], P = 0.01), while no significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…In spite of recent advances, the ideal surface modification of titanium implant for optimal osseointegration is yet an unresolved issue 30,31 . In humans, a titanium implant generally involves a prolong period of 3-4 months to integrate with bone [32][33][34] . Moreover, it has been claimed that regeneration of osseous tissue in rabbit study models are rather swift and all events related to healing may span for a period of approximately six weeks 32,35 .…”
Section: Discussionmentioning
confidence: 99%
“…In spite of recent advances, the ideal surface modification of titanium implant for optimal osseointegration is yet an unresolved issue 30,31 . In humans, a titanium implant generally involves a prolong period of 3-4 months to integrate with bone [32][33][34] . Moreover, it has been claimed that regeneration of osseous tissue in rabbit study models are rather swift and all events related to healing may span for a period of approximately six weeks 32,35 .…”
Section: Discussionmentioning
confidence: 99%
“…In the past 50 years, implant dentistry for fully edentulous mandibles and maxillae has evolved from conventional delayed loading (3–6 months) to early loading (6–8 weeks) or immediate loading [ 9 , 10 ]. The breakthrough in loading protocol was achieved by early implant anchorage with surrounding bone tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The sand-blasting and acid etching (SLA) method achieves micron and submicron scale topography for implant fixation. Previous clinical studies have reported the characteristics of SLA implants, which can restore bone defects after a healing period of 6–8 weeks [ 9 , 10 ]. Although SLA treatment for bone fixation does not alter the surface composition of titanium, SLA-treated surfaces belong to hydrophobic properties.…”
Section: Introductionmentioning
confidence: 99%
“…From the results, they concluded that higher risk of failure is associated with the immediate loaded dental implants. Zhu et al 21 evaluated the clinical differences between the outcome of immediate and delayed loading of dental implants. From the results, they concluded that despite of the convenience and comfort of the immediate loaded dental implants, clinical outcome comparable to conventional method of loading of dental implants cannot be reached.…”
Section: Discussionmentioning
confidence: 99%